Thermal decomposition and stability in a series of heterobimetallic carbonyl compounds of the type [Fe(CO)4(HgX)2] (X=Cl, Br, I) - Zamian, José Roberto; Mauro, Antonio Eduardo; Nunes, Carolina Coimbra; de Almeida, Eduardo Tonon (Eclética Química, 2000)
Heterobimetallic carbonyl compounds of the type [Fe(CO)4(HgX)2] (X= Cl, Br, I), which have metal-metal bonds, have been prepared in order to study their thermal stabilities as a function of the halogen coordinated to mercury atoms. The characterization of the above complexes was carried out by elemental analysis, IR and NMR spectroscopies. Their thermal behaviour has been investigated and the final product was identified by IR spectroscopy and by X-ray powder diffractogram.